An empirical analysis of East Asian computer exports - Willem Thorbecke (Asian Development Bank Institute (ADBI), 2009)
For the last 15 years, computers have been the leading export category from East Asia to the rest of the world. They are produced within regional production and distribution networks. Japan; Republic of Korea; and Taipei,China construct sophisticated technology-intensive parts and components and ship them to the People's Republic of China (PRC) and Association of Southeast Asian Nations (ASEAN) for processing by lower-skilled workers and re-export. This paper presents evidence that exchange rate appreciations in countries supplying parts and components to East Asian assembly economies would curtail computer exports, while exchange rate appreciations in assembly economies would not. The evidence also indicates that decreases in income in importing countries would significantly reduce computer exports. These findings imply that if growth remains slow in the rest of the world, computer exports will no longer be able to play the same role as an engine of growth. This evidence thus provides impetus to create initiatives to promote the demand for final goods in the region.
Keywords: F32; F41; 330